Hemoparásitos en aves de zonas urbanas y periurbanas de la ciudad de Iquitos y Nauta, Loreto-Perú - Valdivia Zavaleta, Xiomara Almendra (2023)
The objective of this research was to determine the hemoparasites in birds of urban and periurban areas of the cities of Iquitos and Nauta, in order to make an initial diagnosis of the avian parasitic situation in Ammodramus aurifrons, Cacicus cela, Thraupis episcopus and Troglodytes aedon. The population consisted of these four species of birds from urban and peri-urban areas of the cities of Iquitos and Nauta, establishing a sample of 240 specimens captured, 74 of A. aurifrons, 39 of C. cela, 95 of T. episcopus and 32 of T. aedon. Mist nets were used to capture the birds. Blood samples were taken for subsequent analysis by conventional microscopy and Polymerase Chain Reaction (PCR). The prevalence indice found was low, 25% (60/240) of birds were positive for hemoparasites by microscopy and PCR. Plasmodium spp. (11.66%) had the highest prevalence, followed by Plasmodium/Haemoproteus (11.25%), Haemoproteus spp. (3.33%), microfilariae (2.5%) and Leucocytozoon sp. (1.5%). The most infected bird species were C. cela (43.59%) and A. aurifrons (40.54%). Regarding similarity indice, differences were found between hemoparasites in birds from urban versus peri-urban areas in Iquitos, with Plasmodium spp. and Plasmodium/Haemoproteus being the most present in peri-urban areas; while in Nauta there was no difference in birds from urban and peri-urban areas, with these hemoparasites being present in both study areas. It is concluded that the avian hemoparasites recorded differ across urban and peri-urban areas of the cities of Iquitos and Nauta. Leucocytotozoon sp. was reported for the first time in birds in the department of Loreto.